A Molecular Dynamics Study on Au - Ciftci, Yasemin Oztekin; Colakoglu, Kemal; Ozgen, Soner (Intech Europe, 2012)
[Abstract Not Available]
Keywords: Elastic-Constants; Transition-Metals; Phase-Diagram; Fcc; Dependence; Amorphization; Temperature; Simulations; Pressure; Alloys